Pengolahan Pupuk Organik Padat Sebagai Upaya Pengurangan Penggunaan Pupuk Kimia di Kelurahan Ngadirejo Kecamatan Kepanjen Kidul, Kota Blitar - Dini Hiqmatul Hayati; Fatima Azrina Pramesthi; Naila Nadhifa Qotrunnada; Nurul N; Prasmita Dian Wijayati (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Kelurahan Ngadirejo is a kelurahan which is a fertile area suitable for agriculture. The agricultural land in this region is quite extensive which indicates that there is also a high demand for fertilizers used in agricultural processing. The cost of buying fertilizer to the total cost of production of agricultural products ranges from 15-30%. Fertilizer is one of the needs for farmers, fertilizer can help meet the nutrient needs needed by plants so they can produce well. However, the continuous use of chemical fertilizers can damage soil elements, thereby disrupting plant growth. Therefore, community service activities were carried out by socializing the manufacture of solid organic fertilizer in the Setia Kawan V Farmers Group, Ngadirejo Village, Blitar City. This socialization on the manufacture of solid organic fertilizer provides an overview of several ways or techniques for making organic fertilizer with different basic ingredients so that it can benefit the community, especially farmers. This service activity is carried out by providing material in the form of leaflets or brochures, FGD (Focus Group Discussion) and the practice of making solid organic fertilizer directly.